Enzyme responsive surfaces: towards a smart cell-material interface - Canning, Anne (2018)
Enzymes are promising stimuli for the development of responsive biomaterials for biomedical applications. Enzymes are inherently present in the biological environment thus cleverly designed materials for biomedical applications may require no external stimuli to ellicit the required material response. They have been targeted as stimuli in self assembly of bulk materials owing to the material changes in chemical composition afforded by the enzyme interaction. The first examples of autonomous self-regulated drug delivery systems have been reported via the development of reversible enzyme responsive materials that undergo a material change regulated by the enzymes in their environment. Although enzyme responsive surfaces have been reported there are no examples of reversible enzyme response surfaces.